+0  
 
0
318
1
avatar

Use the graphs of f(x) = 2/x  and g(x) = 1/-3-x to determine the solutions to f(x) = g(x).

 

 

A)(-2, -1)

B)(-2, 1)

C)(2, 1)

D)(2, -1)

 

 

Simplify the expression.

x^2 + x - 6/x^2 - 4 * x^2 - 9/x^2 + 6x + 9

 

 

A)

x - 3/x + 2

B)

x + 3/x - 2

C)

x - 2/x + 3

D)

x + 2/x - 3

 Aug 16, 2017
 #1
avatar+98197 
+1

 

It looks as though f(x) = g (x ) at  (-2, -1)

 

 

[x^2 + x - 6] / [x^2 - 4] *  [x^2 - 9] / [x^2 + 6x + 9]     factor numerators and denominators

 

[ (x + 3) (x - 2)] / [ (x + 2) ( x - 2) ]  *  [ ( x + 3) ( x - 3) ] / [ (x + 3) ( x + 3) ]

 

Simplifies to

 

[ ( x + 3) ] / [ ( x + 2) ]  *  [ ( x - 3) ] / [ ( x + 3) ]    =

 

[ ( x + 3) ] / [ ( x + 3) ] * [ x - 3) ] /  [ ( x + 2) ]  =

 

[ ( x - 3) ] / [ ( x + 2) ]

 

 

cool cool cool

 Aug 16, 2017

34 Online Users

avatar